Intelligent control of a pole balancing robot - Kyaw, Aung Aung. (2008)
In this reports, an intelligent controller capable of balancing the pole mounted on the motorized robot while performing the desired movement is designed and developed. The controller is designed and developed for both static mode and dynamic mode using the fuzzy logic controller.